2011
DOI: 10.1007/s10457-011-9371-x
|View full text |Cite
|
Sign up to set email alerts
|

Folk perception of sexual dimorphism, sex ratio, and spatial repartition: implications for population dynamics of Sclerocarya birrea [(A. Rich) Hochst] populations in Benin, West Africa

Abstract: In Sub-Saharan Africa, indigenous fruit trees play vital roles in nutrition and food security particularly, in food shortage times. Sclerocarya birrea subsp. birrea, an indigenous dioecious fruit tree is such a resource with strong multipurpose use characteristics in semi-arid zones of West Africa. We assessed sex ratio, spatial distribution among male and female adult trees using second-order spatial statistics and assessed folk perception of dioecism among the natural populations in protected areas and surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Field observations of hermaphrodite flowers and fruit on rare male plants, corroborated the allegation of some farmers that male plants produced rare fruits in some seasons. Gouwakinnou et al (2011) also noted that male plants of hermaphrodite flowers bore fruits. This study has specifically shown that there exist hermaphrodite plants that bear a few male flowers.…”
Section: Discussionmentioning
confidence: 96%
“…Field observations of hermaphrodite flowers and fruit on rare male plants, corroborated the allegation of some farmers that male plants produced rare fruits in some seasons. Gouwakinnou et al (2011) also noted that male plants of hermaphrodite flowers bore fruits. This study has specifically shown that there exist hermaphrodite plants that bear a few male flowers.…”
Section: Discussionmentioning
confidence: 96%
“…The development of fruits and viable seed through selfing treatment is an indication of hermaphrodite flowers with functional male and female organs on the same flower [15]. Even though S. birrea is generally described as dioecious tree species reports have indicated the existence of isolated cases of monoecy within the species [11,33].…”
Section: Pollination By Selfing (Hermaphrodite Flowers Only)mentioning
confidence: 99%
“…Where there were more trees flowering, the tendency is towards unity. Nevertheless, a greater number of studies in dioecious plants have attributed sex biasness to sex-differentiated mortality to stressful habitats [22] with female's plants investing more in reproductive activities and less in growth and maintenance compared to male [15].…”
Section: Sex Ratiomentioning
confidence: 99%
See 2 more Smart Citations